2016
DOI: 10.1177/2372732215623553
|View full text |Cite
|
Sign up to set email alerts
|

Research and Policy Considerations for English Learner Equity

Abstract: Equity TweetResearch suggests revisions to how English learner students are classified, tracked, taught, and tested. Key Points• • Research suggests that many currently implemented education policies likely contribute to inequitable access and outcomes for English learners (ELs). AbstractEnglish learners (ELs), students from a home where a language other than English is spoken and who are in the process of developing English proficiency themselves, represent more than 10% of the U.S. student population. Oftent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…This observation is especially the case given that the criteria I used may not be equally important to the potential validity or reliability of a KEA for this purpose. At the same time, because research data can potentially help policymakers evaluate whether education policies and practices are adequate for supporting EL students' academic outcomes (Robinson‐Cimpian et al, ), the study's results also suggest three areas for future research.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This observation is especially the case given that the criteria I used may not be equally important to the potential validity or reliability of a KEA for this purpose. At the same time, because research data can potentially help policymakers evaluate whether education policies and practices are adequate for supporting EL students' academic outcomes (Robinson‐Cimpian et al, ), the study's results also suggest three areas for future research.…”
Section: Discussionmentioning
confidence: 90%
“…Given this interrelated policy context, it is important from an educational equity perspective to examine to what extent KEAs are valid and reliable for all kindergartners (Goldstein & Flake, ). Such an examination can shed light on needed EL‐related education policy and practice revisions as well (Abedi, Hofstetter, & Lord, ; Robinson‐Cimpian, Thompson, & Umansky, ). However, researchers have not yet looked across specific state KEAs and hypothesized to what extent these measures are likely to produce valid and reliable evidence of what EL students know and can do, much less tested out such hypotheses in a methodologically rigorous manner.…”
mentioning
confidence: 99%
“…ELLs are, by definition, in the process of acquiring English proficiency, and once they reach proficiency, they leave the category. Further, widely-utilized assessments may understate ELLs' academic skills, since these assessments typically assume a baseline of fluency in English that ELLs have not yet acquired (Abedi, 2008;Robinson-Cimpian, Thompson, & Umansky, 2016). Finally, since ELL students are often segregated from non-ELL peers, they often have fewer opportunities to learn rigorous educational content than their non-ELL students (Callahan, 2005;Umansky, 2016).…”
Section: School Studentsmentioning
confidence: 99%
“…Placed in numeral context, more than four million of this population are in the process of developing English and are classified as English learners (U.S. Department of Education, 2015). Robinson-Cimpian, Thompson, and Umansky (2016) contended that English learners (ELs) represent more than 10 percent of the United States student population. Moreover, the National Center for English Language Acquisition (2011) found that, more than one out of every four children in the United States are from immigrant families, and in most cases, they speak a language other than English at home.…”
Section: Accordingmentioning
confidence: 99%